Hardware-in-the-loop simulation of automatic steering control for double lane change and sine steer manoeuvres. (9th July 2012) - Ping, Em Poh; Hudha, Khisbullah; Jamaluddin, Hishamuddin
This paper presents a 9-Degree of Freedom (DOF) vehicle model combined with a closed loop driver model for developing vehicle lateral control. The driver model was developed to control the steering angle and uses predefined path as a reference for the control input. The outer-loop and inner-loop controllers were evaluated by simulation using ISO Double Lane Change (DLC) and sine steer manoeuvres. Both of the controller's Software-In-The-Loop Simulations (SILS) were validated through the Hardware-in-the-Loop Simulation (HILS). The SILS and HILS results show that the proposed driver model is capable of improving lateral path deviation error and lateral path manoeuvres significantly.